2020
DOI: 10.3389/fphys.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Regional Lung Deformation Using Four-Dimensional Computed Tomography: A Comparison of Conventional and Oscillatory Ventilation

Abstract: Mechanical ventilation strategies that reduce the heterogeneity of regional lung stress and strain may reduce the risk of ventilator-induced lung injury (VILI). In this study, we used registration of four-dimensional computed tomographic (4DCT) images to assess regional lung aeration and deformation in 10 pigs under baseline conditions and following acute lung injury induced with oleic acid. CT images were obtained via dynamic axial imaging (Siemens SOMATOM Force) during conventional pressure-controlled mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Considering the observed alterations in mechanical properties of fetal lung tissue under compression together with the impact of hydrostatic pressure on ENaC activity in fetal distal lung epithelia, we expect that ventilation techniques must carefully address correlations between tidal volumes, pressures and frequencies. As demonstrated by Kaczka et al (2015) and Herrmann et al (2020), in contrast to HFOV and conventional MV, multi-frequency oscillatory ventilation modalities (MFOV) might provide improved lung-protective ventilation by reducing strain magnitudes and spatial gradients of strain.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the observed alterations in mechanical properties of fetal lung tissue under compression together with the impact of hydrostatic pressure on ENaC activity in fetal distal lung epithelia, we expect that ventilation techniques must carefully address correlations between tidal volumes, pressures and frequencies. As demonstrated by Kaczka et al (2015) and Herrmann et al (2020), in contrast to HFOV and conventional MV, multi-frequency oscillatory ventilation modalities (MFOV) might provide improved lung-protective ventilation by reducing strain magnitudes and spatial gradients of strain.…”
Section: Discussionmentioning
confidence: 99%
“…All experimental procedures were approved by the University of Iowa Institute for Animal Care and Use Committee (Protocol Number 5061428). Two other studies of respiratory mechanics, involving regional dynamic deformation (Herrmann et al, 2020a) and gas transport (Herrmann et al, 2021), were previously published using data collected from the subjects used in this study. Eleven pigs were used in this study, weighing between 9 and 13 kg.…”
Section: Methodsmentioning
confidence: 99%
“…The goal of this study was to quantify regional rates of lung deaeration during passive exhalation, using four-dimensional computed tomography (4DCT) dynamic imaging ( Herrmann et al, 2017 ) and 4D image registration ( Zhao et al, 2016 ; Herrmann et al, 2020a ) to track localized aeration changes with high spatial resolution. In addition to assessment of aeration based on CT density, it is also possible to account for specific gas volume changes using an intensity-corrected Jacobian determinant, which is more strongly correlated to specific ventilation ( Ding et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…A saline lavage model of sheep found that transpulmonary pressure was lowest at 9 Hz, which coincided with the lowest degree of lung inflammation ( Liu et al, 2013 ). A porcine model of oleic acid lung injury found greater lung strain at lower frequency, with the lowest strain noted at a frequency of 20 Hz ( Herrmann et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%